Antibiotic Resistance Patterns of Pseudomonas spp. Isolated From Raw Milk Revealed by Whole Genome Sequencing - Meng, Lu; Liu, Huimin; Lan, Tu; Dong, Lei; Hu, Haiyan; Zhao, Shengguo; Zhang, Yangdong; Zheng, Nan; Wang, Jiaqi (Frontiers in Microbiology, 2020)
Psychrotrophic bacteria in raw milk are most well-known for their spoilage potential and the economic losses they cause to the dairy industry. Food-related psychrotrophic bacteria are increasingly reported to have antibiotic resistance features. The aim of this study was to evaluate the resistance patterns of Pseudomonas spp. isolated from bulk tank milk. In total, we investigated the antibiotic susceptibility profiles of 86 Pseudomonas spp. isolates from raw milk. All strains were tested against 15 antimicrobial agents. Pseudomonas isolates were most highly resistant to imipenem (95.3%), followed by trimethoprim-sulfamethoxazole (69.8%), aztreonam (60.5%), chloramphenicol (45.3%), and meropenem (27.9%). Their multiple antibiotic resistance (MAR) index values ranged from 0.0 to 0.8. Whole genome sequencing revealed the presence of intrinsic resistance determinants, such as BcI, ampC-09, blaCTX-M, oprD, sul1, dfrE, catA1, catB3, catI, floR, and cmlV. Moreover, resistance-nodulation-cell division (RND) and ATP-binding cassette (ABC) antibiotic efflux pumps were also found. This study provides further knowledge of the antibiotic resistance patterns of Pseudomonas spp. in milk, which may advance our understanding of resistance in Pseudomonas, and suggests that antibiotic resistance of Pseudomonas spp. in raw milk should be a concern.